The W-shaped model of professional competencies for the Fourth Industrial Revolution and its relevance to honors programs - Beata Jones; Albert Pilot; Pierre van Eijl; Josephine Lappia (Hanze UAS, 2020)
As the world is undergoing the Fourth Industrial Revolution (4IR), the fusing of physical, digital, and biological worlds with the new technologies, we experience a profound impact of this revolution on the labor markets and subsequent career planning of students. The new economic reality created by 4IR calls for immediate action in the world of higher education. The purpose of this paper is to advocate for new key competencies that university students will need to thrive in the new economy. These competencies include human literacy, digital fluency, hyper-learning, and systems and design thinking. Together, they are presented as the 'W- shaped 4IR Competency Model'. This model combines previously published opinions about the topic from various educational futurists who have tackled the issue. This paper includes a call to action for universities to address the skills gap challenge of college graduates and rethink their value propositions. As honors programs are the breeding ground for innovation, universities might consider starting to test the robot-proof, twenty-first-century curricula with the smaller honors cohorts and then consider the curricular transfer to the mainstream educational programs. We urge honors educators and administrators around the world to adopt curricula that will make their graduates 'robot-proof' and able to thrive in the new economy for decades to come.